Cesare Pavese en Los diarios de Emilio Renzi de Ricardo Piglia (El Hilo de la Fabula, 2019)
Ricardo Piglia was a diarist and so was Cesare Pavese. Named Emilio Renzi, the Argentinian writer started recording his life in «the series of black notebooks» by the end of 1957. In 2005, the writer reorganized and completed the original material under the name of Los diarios de Emilio Renzi. Inanalysing the inception of Piglia’s diary, the reader can perfectly trace back Cesare Pavece’s initiative and model character in Il mestiere di vivere. Diario 1935–1950 (1952). Being a son and grandson of Italians, Renzi recognizes himself in his diary as an Italian–Argentinian writer who regards Cesa-re Pavese as his cult author. Piglia was able to give voice to Emilio Renzi out of his attentive and recurring reading of Pavese’s diary, an example of literature as an ordering principle of experience. This work configures an inquiry aiming at demonstrating the paradigmatic value of Pavese’s diary for Piglia as a finished fusion model of art and life.
Keywords: Diary; literatura; life